PERAN KEPUASAN MEMEDIASI PENGARUH PENGALAMAN PELANGGAN DAN KEPERCAYAAN TERHADAP NIAT BELI ULANG SECARA ONLINE - Ardelia, Ni Putu Dila; Rahyuda, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Technological developments have had a major impact on the business world, one of which is the development of a new type of business, namely e-commerce. As one of the largest marketplaces in Indonesia, Shopee is also very aggressive in promoting its users. This study aims to explain the effect of customer experience on customer satisfaction, the effect of trust on customer satisfaction, the effect of customer experience on repurchase intentions, the effect of trust on repurchase intentions, the effect of customer satisfaction on repurchase intentions, the role of customer satisfaction mediating the effect of customer experience on intention. repurchase, the role of customer satisfaction mediates the effect of trust on repurchase intentions on the Shopee.co.id online site. The study used a sample of 75 people, the method used in the sample was non-probability sampling method, the type of data source used was qualitative and quantitative data, data collection was carried out by distributing questionnaires and data analysis techniques used descriptive statistics. The results of the analysis of the study found that customer experience has a positive and significant effect on customer satisfaction. Trust has a positive and significant effect on customer satisfaction. Customer experience has a positive and significant effect on repurchase intention. Trust has a positive and significant effect on repurchase intentions. Customer satisfaction has a positive and significant effect on purchase intention. Customer satisfaction is able to mediate the effect of customer experience on repurchase intention. Customer satisfaction is able to mediate the effect of trust on repurchase intentions